109k views
3 votes
PLEASEEEE HELPPPPP IM BEGGING SOMEONE HELPPP PLEASEEEEEEEEE PLEASEEEEEEEE​

PLEASEEEE HELPPPPP IM BEGGING SOMEONE HELPPP PLEASEEEEEEEEE PLEASEEEEEEEE​-example-1

2 Answers

1 vote
X= -1
Y= 6
That’s the answer
User Jordan Miner
by
5.2k points
2 votes

Answer:

x = -1

y = 6

Explanation:

We can multiply the second equation by two, so we can have opposite y terms:

2 (3x - 2y = -15)

6x - 4y = -30

Now, we can add the equations, and the y terms can cancel out:

7x + 4y = 17

+ 6x - 4y = -30

13x = -13

x = -1

Now, we can plug in x:

3(-1) - 2y = -15

-3 - 2y = -15

-2y = -12

y = 6

User Om Sao
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.